A Study of the Development of STEM-Based Science Teaching Materials to Improve Learning Outcomes For Elementary School Students in the 2020-2025 Range - Solihawati, Sofi; Muh. Sholeh; Subali, Bambang; Widiarti, Nuni (Journal of Innovation and Research in Primary Education, 2025)
Science, Technology, Engineering, and Mathematics (STEM) has been widely implemented in the learning process of Natural Sciences (IPA) to encourage improvements in student learning outcomes. This study aims to examine the development of STEM-based IPA teaching materials in improving the learning outcomes of elementary school students between 2020 and 2025. This study was conducted using the Systematic Literature Review (SLR) method by reviewing various studies and journals discussing the effectiveness of implementing STEM-based science teaching materials in science education at elementary schools. Through systematic review, 19 articles were identified, covering aspects such as teaching material design, teaching methods, measurability of learning outcomes, educational levels, as well as challenges and opportunities in implementing the STEM approach. The articles were obtained from various databases such as Google Scholar, ResearchGate, and SINTA-accredited journals. The results of the study indicate that the use of STEM-based science teaching materials significantly promotes improvements in conceptual understanding, critical thinking skills, skills in conducting scientific processes, student creativity, scientific communication, and student collaboration. From this study, it can be concluded that the development of STEM-based science teaching materials has great potential in improving the learning outcomes of elementary school students.